PELAKSANAAN PERJANJIAN KREDIT MODAL USAHA ANTARA PT.BANK PERKREDITAN RAKYAT UNISRITAMA DENGAN NASABAH DI KOTA PEKANBARU - Teti Nadya; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Banking is a source of funds in the form of the granting of credit facilities for the community of individuals or business entities to meet the needs business so his business is increasing and evolving. The granting of credit facilities capital stock Of PT. Bank Rakyat Unisitama Soweto to the customer is done through a credit agreement by applying the precautionary principle and risk management credit, but in practice not everything runs smoothly in accordance with the exchanged so that these conditions cause the onset of the credit issues that must be resolved by PT. Bank people's Unisitama Of Pekanbaru.As for the purpose of this research is to know the implementation of the agreement between venture capital credit Pt. Bank Rakyat Unisritama Of Pekanbaru with customers in the city of Pekanbaru 2014 , to know the obstacles the implementation of the venture capital credit agreement between PT. Bank Rakyat Unisritama Of Pekanbaru with customers in the city of Pekanbaru 2014 and the efforts made in addressing the the barriers such.This type of research is sociological research i.e. Research directly on a location or place that is examined with primary and secondary data sources, data collection techniques by conducting interviews and literature review dan descriptive qualitative data analysis as well as methods of deductive conclusions made in withdrawal.Research results showed the execution of the agreement credit business capital between pt. Bank Of Unisritama the people of Soweto dengan customers in the city of Pekanbaru 2014, starting with the application for credit, checks, file verification, on the sport, credit analysis, credit decisions, credit administration, credit disbursements and obligations of the customer. Barriers to the implementation of the Covenant, namely venture capital credit application process takes a long time, installment credit not everything smoothly, construction and supervision of the customer less, socializing less credit. The effort of overcoming the the resistance that is increasing resources account officer, increases the prospective customer knowledge, coaching and supervision insufficient.Pt. Bank Rakyat Unisritama Of Pekanbaru we recommend that you increase the number of qualified accounts officer recruitment through objective and transparent to the customer credit employee venture capital, pt. Bank Rakyat Unisritama Of Soweto helped implementation of credit business capital. Pt. Bank Rakyat Unisritama Of Pekanbaru the budget provides for special credit promotions business capital cost in order for the community who have a small business and micro know about venture capital credit.Keywords: Credit – Venture Capital – Banking